DISCHARGE, SUBSTRATE TYPE AND TEMPERATURE AS FACTORS AFFECTING GASTROPOD ASSEMBLAGES IN SPRINGS IN NORTHWESTERN BOSNIA AND HERZEGOVINA - Dmitrović, Dejan; Savić, Ana; Pešić, Vladimir (Archives of Biological Sciences, 2016)
In this study, we analyzed changes to gastropod assemblages with regard to the seasonal variations of discharge, substrate composition and temperature in 19 springs in northwestern Bosnia and Herzegovina. Six aquatic gastropod species were identified, including Bosnidilhia vreloana Boeters, Glöer & Pešić, 2013 and Islamia dmitroviciana Boeters, Glöer & Pešić, 2013, two species endemic for the studied area. Surprisingly, we did not observe a significant influence of discharge on the composition of gastropod assemblages in the studied springs. This could mean that gastropod assemblages in the springs examined are well adapted to intermittent conditions (i.e. fluctuations in discharge). The results of canonical correspondence analysis (CCA) showed that specific substrate types can be good predictors for the occurrence of particular species. Interestingly, we found that spring specialists such as Bythinella schmidti and Islamia dmitroviciana also inhabit springs with intermittent dry periods. The studied springs should be considered at risk and some of their gastropod dwellers, such as the endemics Bosnidilhia vreloana and Islamia dmitroviciana, are possibly endangered, requiring conservation planning to protect these spring habitats. Key words: springs; intermittent springs, gastropods; discharge; substrate types Received: October 9, 2015; Revised: November 3, 2015; Accepted: November 10, 2015; Published online: May 23, 2016